The Better Angels : Five Women Who Changed Civil War America - Plumb, Robert C. (Book collections on Project MUSE., 2020)
"This multi-layered biography examines five remarkable women who made important contributions to the Union cause at various stages before, during, and following the defining years of the American Civil War"--